Developing Students’ Critical Thinking Through High Order Thinking (HOT) Question In Reading Comprehension - Wawat Srinawati; Meita Lesmiaty Khasyar; Alvi Nurfuadi (JURNAL SERAMBI ILMU, 2020)
The writer used qualitative research qualitative research is a research studies that investigate the qualitiy of relationship, activities, situations or materials are frequently. The research was conducted on 24th July at SMA Negeri 1 Cibungbulang and the sample were 16 samples. In doing this research, the writer took the data using triangulation technique by collecting the data from observation, questionnaire and interview. This technique was used because the writer wanted to examine the data credibility and also avoid the bias data in research. The overall attitude of respondents interest in English and reading is in the category of positive attitudes. writer gave the questionnaire to the students who were being respondents or samples for the research. The questionnaire were 20 statements and devided into 3 categories, those are interest; perception/critical thinking and HOTS understanding. 20 students who were being the sample answered the statements it was very vary. This classroom observation showed that in skill gathering, evaluating information and ideas students got 60% with teacher’s guide and 40% with students’ initiation This is indicated by the total score of respondents which amounted to 393 and lies between a score of 300 (median) and 400 (quartile 3), which is the score limit in the positive attitude category. It appeared that the attitudes of each respondent are spread in the very positive attitude 40%, positive attitude 55% and negative attitude 5%. Each respondent's attitudes about students' interest in English, reading and text spread in the very positive attitude category 40%, positive attitude 50% and negative attitude 10%.